Development of entrepreneurship based on the synergic influence of clusters in the regions - Kurbanov Bobokulovich, Alisher (THE INNOVATION ECONOMY, 2024)
The article analyzes the evolution of clusters in the economy and the methodological approaches of scientists. It is deeply analyzed that the rise of the wave of clusters in our time is mainly associated with the processes of fragmentation of vertically integrated companies and the reason for this is the sharp increase in product complexity. First of all, as a result of the multiple increase in the number and range of intermediate products and components used in the assembly of final products in the industry, it was justified that the concentration of all enterprises under one roof is not a realistic option. The cluster economy makes it possible to create an environment of creativity and ensure the formation of innovative activities. In world experience, there are two main approaches to the formation of clusters. Firstly, the classical liberal or AngloSaxon approach, proposed in the 80s and 90s, is carried out within the framework of “free market” mechanisms based on the self-organization of M.Porter. The second is an analysis of the modern European approach called “Poles”, based on competitive business and cooperation between central and local authorities, and also shows the directions for applying the synergistic effect of clusters and the trigger effect in economic entities of our republic. The current state of clusters is analyzed, conclusions and proposals are presented.